Cryptic speciation yields remarkable mimics: a new genus of sea slugs that masquerade as toxic algae (Caulerpa spp.) - Krug, Patrick J.; Wong, Nur Leena Wai Sin; Medina, Melanie R.; Gosliner, Terrence M.; Valdes, Angel A. (Wiley-Blackwell Publishing, 2018)
“Cryptic” can refer to species that match their background through camouflage or disruptive colouration, or in taxonomy to externally similar but unrecognized congeners. In adaptive resemblance, organisms resemble parts of a larger host animal or plant on which the mimic is highly cryptic. Mimetic lineages that radiate onto superficially similar hosts may contain cryptic species in both senses: taxa that are difficult to detect, and challenging for taxonomists to distinguish. Here, we describe a new genus and four species of herbivorous sea slugs (Gastropoda, Heterobranchia, Sacoglossa), including remarkable mimics of toxic green algae (Caulerpa spp.) on which the slugs feed. The long‐recognized Stiliger smaragdinus Baba 1949 is highly mimetic of “sea grapes” (Caulerpa racemosa‐lentillifera), but phylogenetic analyses of four genes indicated Stiliger was polyphyletic: the name‐bearing species grouped within Placida, whereas Caulerpa‐mimetic lineages were phylogenetically distinct. We erect the genus Sacoproteus gen. n. for S. smaragdinus (Baba 1949), and describe four new species: S. nishae sp. n. from the Indo‐Pacific, which mimics Caulerpa chemnitzia; Sacoproteus yhiae sp. n. and Sacoproteus browni sp. n. from southern Australia, which mimic Caulerpa cactoides and Caulerpa gemminata; and Sacoproteus thomasleei sp. n., a non‐mimetic west Pacific species that shared key features. Stiliger s.s. and Placida species show crypsis and aposematism but not host mimicry, although Stiliger spp. feeding on undefended algae may be Batesian mimics. Investigating the ecology and biogeography of Sacoproteus gen. n. will yield insight into how selection generates such extraordinary examples of adaptive resemblance in the marine realm.